Multinational location strategy - Rugman, Alan M.; Mucchielli, Jean Louis (Emerald, 1998)
This examination of multinational location strategy focuses on the areas of economics, management and policy. It discusses issues such as regionalism and international trade; location patterns, local content rules and foreign direct investment; and, plant location in Eastern European countries.
Includes index.
Keywords: International business enterprises -- Management.; Strategic planning.; Global economics.; elektronické knihy; electronic books